Human Teeth-Derived Bioceramics for Improved Bone Regeneration - Ki-Taek Lim; Dinesh K. Patel; Sayan Deb Dutta; Han-Wool Choung; Hexiu Jin; Arjak Bhattacharjee; Jong Hoon Chung (Nanomaterials, 2020)
Hydroxyapatite (HAp, Ca10(PO4)6(OH)2) is one of the most promising candidates of the calcium phosphate family, suitable for bone tissue regeneration due to its structural similarities with human hard tissues. However, the requirements of high purity and the non-availability of adequate synthetic techniques limit the application of synthetic HAp in bone tissue engineering. Herein, we developed and evaluated the bone regeneration potential of human teeth-derived bioceramics in mice′s defective skulls. The developed bioceramics were analyzed by X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, and scanning electron microscopy (FE-SEM). The developed bioceramics exhibited the characteristic peaks of HAp in FTIR and XRD patterns. The inductively coupled plasma mass spectrometry (ICP-MS) technique was applied to determine the Ca/P molar ratio in the developed bioceramics, and it was 1.67. Cytotoxicity of the simulated body fluid (SBF)-soaked bioceramics was evaluated by WST-1 assay in the presence of human alveolar bone marrow stem cells (hABMSCs). No adverse effects were observed in the presence of the developed bioceramics, indicating their biocompatibility. The cells adequately adhered to the bioceramics-treated media. Enhanced bone regeneration occurred in the presence of the developed bioceramics in the defected skulls of mice, and this potential was profoundly affected by the size of the developed bioceramics. The bioceramics-treated mice groups exhibited greater vascularization compared to control. Therefore, the developed bioceramics have the potential to be used as biomaterials for bone regeneration application.